Multikulturalisme di Indonesia: Relevansi Pancasila, Islam, dan Kebangsaan - Nursangadah, Astuti; Fitrah, Putri Fauziatul; Agustiningsih, Suci; Husna, Fauziya Nailil; Ni’mah, Umi Khoirun (ALSYS, 2022)
The Indonesian nation is full of religious, social, political and cultural diversity, as well as various others. All the diversity that exists in Indonesia makes this nation called a nation of multiculturalism. Islam has formed a unity in line with human history of more than 15 centuries that have passed. Islamic theology almost never contradicts the validity of culture, except for something that is contrary to human values. Islam also justifies the principle of multiculturalism in accordance with what is contained in the Qur'an. Thus, the events of Islam in Indonesia spread very swiftly and widely. As for the problems that occur in Indonesia, such as Islamic doctrinalism, it is in line with traditional cultural values in Indonesia. The largest Muslim country in the world is Indonesia, which has a distinctive social, cultural, political, linguistic and religious diversity. However, the diversity in Indonesia does not diminish unity and is still able to maintain the integrity of the country. Indonesia has an ideology that people believe in until now, namely Pancasila. There are 5 main values stated in Pancasila, that these values undeniably contain Islamic social values in multiculturalism, manifested by the integration of diversity in the form of (NKRI) or the “Negara Kesatuan Republik Indonesia”.